2022
DOI: 10.3389/fpls.2022.901541
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Wx Genotype, Nitrogen Fertilization, and Temperature on Rice Grain Quality

Abstract: Quality is a complex trait that is not only the key determinant of the market value of the rice grain, but is also a major constraint in rice breeding. It is influenced by both genetic and environmental factors. However, the combined effects of genotypes and environmental factors on rice grain quality remain unclear. In this study, we used a three-factor experimental design to examine the grain quality of different Wx genotypes grown under different nitrogen fertilization and temperature conditions during grai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…It can increase yield, but it also decreases the ECQ of rice [ 18 ]. With the increase through nitrogen fertilizers, the AC of rice decreased [ 17 ]. Thus, we still know less about the relationship between Wx of the key controlling AC gene and nitrogen.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It can increase yield, but it also decreases the ECQ of rice [ 18 ]. With the increase through nitrogen fertilizers, the AC of rice decreased [ 17 ]. Thus, we still know less about the relationship between Wx of the key controlling AC gene and nitrogen.…”
Section: Discussionmentioning
confidence: 99%
“…The homozygous T2 lines were used for expression detection and trait collection. The copy number of the transgene in the transgenic rice plants was determined using real-time PCR according to Zhang et al [ 17 ]. The primers are listed in Table S3 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Wx encodes GBSSI, which controls the synthesis of amylose, and is the primary determinant of rice eating, cooking and appearance quality (Zhang et al, 2021a; Zhou et al, 2021). Some studies showed that Wx plays a major role in determining storage protein content and flour color (Tan et al, 2001; Xia et al, 2022). How Wx modulates storage protein content remains unknown.…”
Section: Integrating Regulators Orchestrating Ssp and Starch Accumula...mentioning
confidence: 99%